Efficacy of transconjunctival approach for the treatment of orbital fractures: A protocol for systematic review and meta-analysis. Issue 29 (17th July 2020) - Qi, Yan-Xiu; Li, Si-ying; Wang, Dong-lan; Zhou, Ping-ping
Abstract: Background: This study aims to assess the efficacy of transconjunctival approach (TCA) for the treatment of orbital fractures (OF) comprehensively and systematically. Methods: In this study, we plan to search electronic databases of Cochrane Library, MEDLINE, EMBASE, Web of Science, Allied and Complementary Medicine Database, Chinese Biomedical Literature Database, China National Knowledge Infrastructure and for relevant randomized controlled trials. All these databases will be searched from inception to the March 1, 2020 without limitations of language and publication status. Two independent authors will carry out study selection, data collection, and study quality assessment. Any disagreements will be resolved by discussion with another author if necessary. The study quality will be assessed using Cochrane risk of bias tool. Statistical analysis will be conducted using RevMan 5.3 software. Results: This study will be the first 1 to exert direct evidence to evaluate the efficacy of TCA for the treatment of OF. Conclusions: The findings of this study will provide an exhaustive view of TCA for the treatment of OF. Study registration number: INPLASY202040154.